Hepatic myofibroblasts promote the progression of human cholangiocarcinoma through activation of epidermal growth factor receptor. Issue 6 (25th October 2013) - Clapéron, Audrey; Mergey, Martine; Aoudjehane, Lynda; Ho‐Bouldoires, Thanh Huong Nguyen; Wendum, Dominique; Prignon, Aurélie; Merabtene, Fatiha; Firrincieli, Delphine; Desbois‐Mouthon, Christèle; Scatton, Olivier; Conti, Filomena; Housset, Chantal; et al.
<x xml:space="preserve">Abstract</x> Intrahepatic cholangiocarcinoma (CCA) is characterized by an abundant desmoplastic environment. Poor prognosis of CCA has been associated with the presence of alpha‐smooth muscle actin (α‐SMA)‐positive myofibroblasts (MFs) in the stroma and with the sustained activation of the epidermal growth factor receptor (EGFR) in tumor cells. Among EGFR ligands, heparin‐binding epidermal growth factor (HB‐EGF) has emerged as a paracrine factor that contributes to intercellular communications between MFs and tumor cells in several cancers. This study was designed to test whether hepatic MFs contributed to CCA progression through EGFR signaling. The interplay between CCA cells and hepatic MFs was examined first in vivo, using subcutaneous xenografts into immunocompromised mice. In these experiments, cotransplantation of CCA cells with human liver myofibroblasts (HLMFs) increased tumor incidence, size, and metastastic dissemination of tumors. These effects were abolished by gefitinib, an EGFR tyrosine kinase inhibitor. Immunohistochemical analyses of human CCA tissues showed that stromal MFs expressed HB‐EGF, whereas EGFR was detected in cancer cells. In vitro, HLMFs produced HB‐EGF and their conditioned media induced EGFR activation and promoted disruption of adherens junctions, migratory and invasive properties in CCA cells. These effects were abolished in the presence of gefitinib or HB‐EGF‐neutralizing antibody. We also showed that CCA cells produced transforming growth factor beta 1, which, in turn, induced HB‐EGF expression in HLMFs. Conclusion: A reciprocal cross‐talk between CCA cells and myofibroblasts through the HB‐EGF/EGFR axis contributes to CCA progression. (Hepatology 2013; 58:2001–2011)